A new Cumulative Damage Model for Fatigue Life Prediction under Shot Peening Treatment - M.Alalkawi, Hussain J.; Al Saraf, Saad A. Khuder; Ali, Abdul-Jabar H. (Al-Khwarizmi Engineering Journal, 2017)
AbstractIn this paper, fatigue damage accumulation were studied using many methods i.e.Corton-Dalon (CD),Corton-Dalon-Marsh(CDM), new non-linear model and experimental method. The prediction of fatigue lifetimes based on the two classical methods, Corton-Dalon (CD)andCorton-Dalon-Marsh (CDM), are uneconomic and non-conservative respectively. However satisfactory predictions were obtained by applying the proposed non-linear model (present model) for medium carbon steel compared with experimental work. Many shortcomings of the two classical methods are related to their inability to take into account the surface treatment effect as shot peening. It is clear that the new model shows that a much better and conservative prediction of fatigue life in comparison with CD and CDM methods. The prediction of the present model gave slightly below the experimental data while the CDM gave overestimate prediction and CD showed strongly underestimates the life of specimens. Keywords: Cumulative fatigue damage, Shot peening, Non-linear model.